"Friend" or Foe? Why People Friend Disliked Others on Facebook. Issue 1 (2nd January 2017) - Vendemia, Megan A.; High, Andrew C.; DeAndrea, David C.
Abstract : This study explores the disconnection that exists between the number of friends and relationships people maintain in their face-to-face interactions and the number of connections people establish on social networking sites. Specifically, we examined the extent to which Facebook users "friend" people they dislike and find annoying on Facebook and the reasons people offer for engaging in these seemingly nonintuitive behaviors. The results indicate that, in a sample of college students (N = 305), the majority of Facebook users are friends with people they dislike on Facebook (61%) and actively read the postings of individuals even though they find their postings annoying (85%). Participants' sex, intensity of Facebook use, and general relational anxiety all independently predicted the occurrence of friending disliked others and actively reading annoying postings. A uses and gratifications framework was adopted to develop a typology of reasons why people engage in these behaviors. Monitoring, surveillance, downward social comparison, and other explanations were provided by participants to account for their behavior on Facebook. How engaging in these online behaviors might affect the psychological well-being of individuals and quality of interpersonal relationships is discussed, and future directions for research are offered.